Barium titanate nanopowders prepared from the modified oxalate co-precipitation method - Pusit Pookmanee (2018)
Barium titanate nanopowders were prepared from the modified oxalate co-precipitation method. Barium chloride dihydrate and potassium titanyl oxalate dihydrate were used as the starting precursors with the mole ratio of Ba:Ti as 1:1. Barium titanyl oxalate complex powders were obtained after adjusting the final of pH of the solution to 1. The precipitates were filtered, washed and dried at 100 °C for 5h. The precipitate powders were calcined at 400-700 °C for 2h. The phase transition was studied by X-ray diffractometry (XRD). Cubic structure of barium titanate was obtained after calcinations at 700 °C for 2h. The morphology and chemical composition were investigated by scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDXS). The range of particle size was 50-100 nm with irregular in shape. The elemental composition of barium, titanium and oxygen showed the characteristic X-ray energy values.